Analysis of Damage to the PGM-FI System in Honda Beat Motorcycle for Maintenance Actions - Viko Pradana Regia; Mukhnizar Mukhnizar; Rizal Abu (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
PGM-FI technology is an electronic fuel injection system from Honda that regulates the supply of fuel and oxygen according to the engine's needs. Finding the best repair solution to address sensor issues in the PGM-FI system is a common challenge that requires a comprehensive understanding of this complex technology. This research falls into the category of technical research, aiming to comprehend the principles, causes of malfunctions, and maintenance of the PGM-FI system on the Honda Beat 110 cc. The instruments used include a tool set, multi-tester, fuel pump tester, pressure gauge, scan tool, and test materials for the Honda Beat PGM FI motorcycle. The research results identify sensor malfunctions based on the code of 7 flashes on EOT/ECT (Engine Oil/Coolant Temperature), 8 flashes on TP (Throttle Position), and 12 flashes on the fuel injection system. These malfunctions are caused by issues in the sensor circuit or resistance. Maintenance steps involve inspecting the sensors using a scan tool and clearing error codes in the ECU. Teknologi PGM-FI merupakan sistem injeksi bahan bakar elektronik dari Honda yang mengatur pasokan bahan bakar dan oksigen sesuai kebutuhan mesin. Menemukan solusi perbaikan terbaik untuk mengatasi masalah sensor pada sistem PGM-FI merupakan tantangan umum yang memerlukan pemahaman menyeluruh tentang teknologi yang rumit ini. Penelitian ini termasuk dalam kategori penelitian teknis, dengan tujuan memahami prinsip-prinsip, penyebab kerusakan, dan perawatan sistem PGM-FI pada Honda Beat 110 cc. Instrumen yang digunakan mencakup set peralatan, multi tester, fuel pump tester, pressure gauge, scan tool, dan bahan uji untuk sepeda motor Honda Beat PGM FI. Hasil penelitian mengidentifikasi kerusakan sensor berdasarkan kode 7 kedipan pada EOT/ECT (Engine Oil/Coolant Temperature), 8 kedipan pada TP (Throttle Position), dan 12 kedipan pada sistem injeksi bahan bakar. Kerusakan ini disebabkan oleh masalah pada rangkaian atau tahanan sensor. Langkah-langkah perawatan melibatkan pemeriksaan sensor menggunakan scan tool dan menghapus kode kesalahan di ECU.